PERANAN PARTAI DEMOKRASI INDONESIA PERJUANGAN DALAM MEMENANGKAN PASANGAN JOKO WIDODO – JUSUF KALLA PADA PEMILU PRESIDEN TAHUN 2014 DI KECAMATAN PONDOK MELATI KOTA BEKASI - Edy Kuncoro; Susilo Utomo; Turtiantoro . (Journal of Politic and Government Studies, 2016)
Abstract Joko Widodo and Jusuf Kalla was one candidate for president and vice president in the last presidential election in 2014. Joko Widodo - Jusuf Kalla promoted by a coalition of several parties calling itself Koalisi Indonesia Hebat. In the las presidential election the victory obtained by this couple. But in some areas there are unique things that need to be studied more deeply. Kecamatan Pondok Melati is one of the 12 subdistricts included in the administrative map of Kota Bekasi. In the last presidential election in 2014 Kecamatan Pondok Melati be the only one in Kota Bekasi couples the ordinal number of 2 Joko Widodo - Jusuf Kalla ahead of couples the ordinal number of 1 Prabowo - Hatta. Although only a narrow lead, the number of votes of Joko Widodo - Jusuf Kalla reached 35 050 votes (50.63%) while the couples the ordinal number of 1 Prabowo - Hatta only get 34 176 (49.37%) votes. This victory did not escape from the figures and the popularity of Joko Widodo, moreover, the majority of people Kecamatan pondok melati is urban people for a living, schools, etc. in the Jakarta area. The geographical condition of the District of Pondok Melati directly adjacent to Jakarta. Another factor is coming from an external figure of a Joko Widodo. In Kecamatan Pondok Melati the mass base of the PDI Perjuangan than that in the Kecamtan Pondok Melati also have local political figures. The political machine created by local political leaders to work in total in securing the base and also get maximum results in your opponent's base.